Towards 0.1mm/yr stability over decades for measuring sea level using tide gauges together with GNSS-based instruments? - Pascal Bonnefond; Olivier Laurain; Pierre Exertier; Michel Calzas; Christine Drezen; Lionel Fichen; Antoine Guillot; Thierry Guinle; Nicolas Picot (Marine Geodesy, 2026)

How useful are mispointing phase SARAL/AltiKa geophysical products for ocean applications? - Suchandra Aich Bhowmick; Aditya Chaudhary; M. Jishad; M. Seemanth; Utkarsh; Neeraj Agarwal; Rashmi Sharma; Honey Gupta; J.V. Thomas; Pascal Bonnefond; J. Verron (Advances in Space Research, 2024)

Validating a New GNSS-Based Sea Level Instrument (CalNaGeo) at Senetosa Cape - Pascal Bonnefond; Olivier. Laurain; Pierre Exertier; Michel Calzas; Thierry Guinle; Nicolas Picot (Marine Geodesy, 2022)

Ocean Integration: The Needs and Challenges of Effective Coordination Within the Ocean Observing System - Adèle Révelard; Joaquín Tintoré; Jacques Verron; Pierre Bahurel; John A. Barth; Mathieu Belbéoch; Jérôme Benveniste; Pascal Bonnefond; Eric P. Chassignet; Sophie Cravatte; Fraser Davidson; Brad deYoung; et al. (Frontiers in Marine Science, 2022)
Understanding and sustainably managing complex environments such as marine ecosystems benefits from an integrated approach to ensure that information about all relevant components and their interactions at multiple and nested spatiotemporal scales are considered. This information is based on a wide range of ocean observations using different systems and approaches. An integrated approach thus requires effective collaboration between areas of expertise in order to improve coordination at each step of the ocean observing value chain, from the design and deployment of multi-platform observations to their analysis and the delivery of products, sometimes through data assimilation in numerical models. Despite significant advances over the last two decades in more cooperation across the ocean observing activities, this integrated approach has not yet been fully realized. The ocean observing system still suffers from organizational silos due to independent and often disconnected initiatives, the strong and sometimes destructive competition across disciplines and among scientists, and the absence of a well-established overall governance framework. Here, we address the need for enhanced organizational integration among all the actors of ocean observing, focusing on the occidental systems. We advocate for a major evolution in the way we collaborate, calling for transformative scientific, cultural, behavioral, and management changes. This is timely because we now have the scientific and technical capabilities as well as urgent societal and political drivers. The ambition of the United Nations Decade of Ocean Science for Sustainable Development (2021–2030) and the various efforts to grow a sustainable ocean economy and effective ocean protection efforts all require a more integrated approach to ocean observing. After analyzing the barriers that currently prevent this full integration within the occidental systems, we suggest nine approaches for breaking down the silos and promoting better coordination and sharing. These recommendations are related to the organizational framework, the ocean science culture, the system of recognition and rewards, the data management system, the ocean governance structure, and the ocean observing drivers and funding. These reflections are intended to provide food for thought for further dialogue between all parties involved and trigger concrete actions to foster a real transformational change in ocean observing.

Coastal sea level rise at Senetosa (Corsica) during the Jason altimetry missions - Yvan Gouzenes; Fabien Léger; Anny Cazenave; Florence Birol; Pascal Bonnefond; Marcello Passaro; Fernando Nino; Rafael Almar; Olivier Laurain; Christian Schwatke; Jean-François Legeais; Jérôme Benveniste (Ocean Science, 2020)
In the context of the ESA Climate Change Initiative project, we are engaged in a regional reprocessing of high-resolution (20 Hz) altimetry data of the classical missions in a number of the world's coastal zones. It is done using the ALES (Adaptive Leading Edge Subwaveform) retracker combined with the X-TRACK system dedicated to improve geophysical corrections at the coast. Using the Jason-1 and Jason-2 satellite data, high-resolution, along-track sea level time series have been generated, and coastal sea level trends have been computed over a 14-year time span (from July 2002 to June 2016). In this paper, we focus on a particular coastal site where the Jason track crosses land, Senetosa, located south of Corsica in the Mediterranean Sea, for two reasons: (1) the rate of sea level rise estimated in this project increases significantly in the last 4–5 km to the coast compared to what is observed further offshore, and (2) Senetosa is the calibration site for the TOPEX/Poseidon and Jason altimetry missions, which are equipped for that purpose with in situ instrumentation, in particular tide gauges and a Global Navigation Satellite System (GNSS) antenna. A careful examination of all the potential errors that could explain the increased rate of sea level rise close to the coast (e.g., spurious trends in the geophysical corrections, imperfect inter-mission bias estimate, decrease of valid data close to the coast and errors in waveform retracking) has been carried out, but none of these effects appear able to explain the trend increase. We further explored the possibility that it results from real physical processes. Change in wave conditions was investigated, but wave setup was excluded as a potential contributor because the magnitude was too low and too localized in the immediate vicinity of the shoreline. A preliminary model-based investigation about the contribution of coastal currents indicates that it could be a plausible explanation of the observed change in sea level trend close to the coast.

Requirements for a Coastal Hazards Observing System - Jérôme Benveniste; Anny Cazenave; Stefano Vignudelli; Luciana Fenoglio-Marc; Rashmi Shah; Rafael Almar; Ole Andersen; Florence Birol; Pascal Bonnefond; Jérôme Bouffard; Francisco Calafat; Estel Cardellach; et al. (Frontiers in Marine Science, 2019)

SARAL/AltiKa Absolute Calibration from the Multi-Mission Corsica Facilities - Pascal Bonnefond; Pierre Exertier; Olivier Laurain; Amandine Guillot; Nicolas Picot; Mathilde Cancet; Florent Lyard (Marine Geodesy, 2015)

Validation of SWH and SSHA from SARAL/AltiKa Using Jason-2 and In-Situ Observations - Suchandra Aich Bhowmick; Rashmi Sharma; K. N. Babu; A. K. Shukla; Raj Kumar; R. Venkatesan; R. M. Gairola; Pascal Bonnefond; Nicolas Picot (Marine Geodesy, 2015)

Calcium signals inhibition sensitizes ovarian carcinoma cells to anti-Bcl-xL strategies through Mcl-1 down-regulation - Marie-Laure Bonnefond; Bernard Lambert; Florence Giffard; Edwige Abeilard; Emilie Brotin; Marie-Hélène Louis; Mor Sény Gueye; Pascal Gauduchon; Laurent Poulain; Monique N’Diaye (Apoptosis, 2015)

Preface - John Lillibridge; Hans Bonekamp; Josh Willis; Pascal Bonnefond (Marine Geodesy, 2012)

Absolute Calibration of Jason-1 and Jason-2 Altimeters in Corsica during the Formation Flight Phase - Pascal Bonnefond; Pierre Exertier; Olivier Laurain; Gwenaele Jan (Marine Geodesy, 2010)